Abstractions (Nature (London), 2009)
The glaciation of Antarctica The manner in which the Antarctic ice sheet first formed, at a time of rapid global climate change about 34 million years ago, has been the subject of considerable speculation. Several lines of evidence point to central Antarctic mountain ranges as the site of the initial ice sheet, but our knowledge of the present ice-sheet topography is highly restricted in the very zone where ice-sheet initiation is most likely: along the subglacial Gamburtsev mountain range at the centre of the present ice sheet. Now a detailed survey and analysis of the morphology of the Gamburtsev mountains has been performed, based on an ice-penetrating radar study conducted over two seasons. The data reveal a mountain landscape initially incised by rivers, then over-deepened by ice movement. The topography — beneath up to 3,000 metres of ice — resembles an exploded version of classic alpine valley topography and seems to have developed more than 34 million years ago, when mean summer temperatures were about 3 °C.